2018
DOI: 10.1071/an16609
|View full text |Cite
|
Sign up to set email alerts
|

The effects of partial substitution of soybean with urea or slow-release urea on finishing performance, meat quality, and digestion parameters of Nellore steers

Abstract: The effects of substituting ~50% of the soybeans in the diet of finishing Nellore steers with either urea (U) and/or slow-release urea (SRU) on the steer performance and meat quality were assessed in two experiments. In the first experiment, 46 Nellore steers in a 104-day experiment (Exp. 1) were fed a Control diet with U or SRU or U+SRU. In Experiment 2 (Exp. 2), digestibility and microbial protein (MCP) synthesis were assessed in four steers by using a 4 × 4 Latin square design with 21-day periods. Four corn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Since the values of the ruminal digestibility are related to the availability of N during the ruminal fermentation, it can be inferred that U+SRU+AA was similar to SBM for the total N release for the ruminal bacteria as no differences were observed for the ruminal digestibility of N among the different sources of N. In addition, the lack of effects observed for the intestinal digestibility of the nutrients showed that the changes in the proportion of the non-protein N of the diets did not cause changes in the nutrient digestion after the abomasum. Therefore, the microbial protein likely met 100% of the metabolisable protein required by the steers (Benedeti et al 2014;Corte et al 2018). Similar to our data, Giallongo et al (2015) found no effect of the SRU supplementation and the SRU plus rumen-protected methionine on the NDF digestibility, the feed intake or the milk production and the quality in the dairy cows.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Since the values of the ruminal digestibility are related to the availability of N during the ruminal fermentation, it can be inferred that U+SRU+AA was similar to SBM for the total N release for the ruminal bacteria as no differences were observed for the ruminal digestibility of N among the different sources of N. In addition, the lack of effects observed for the intestinal digestibility of the nutrients showed that the changes in the proportion of the non-protein N of the diets did not cause changes in the nutrient digestion after the abomasum. Therefore, the microbial protein likely met 100% of the metabolisable protein required by the steers (Benedeti et al 2014;Corte et al 2018). Similar to our data, Giallongo et al (2015) found no effect of the SRU supplementation and the SRU plus rumen-protected methionine on the NDF digestibility, the feed intake or the milk production and the quality in the dairy cows.…”
Section: Discussionsupporting
confidence: 86%
“…Slow-release urea (SRU) products to reduce the rate of ammonia release from U are currently available. Substantial research has been developed to evaluate the effects of these SRU products (Chegeni et al 2013;Benedeti et al 2014;Giallongo et al 2015;Gardinal et al 2017;Corte et al 2018) in cattle. Previous studies found that although SRU released more N than soybean meal (SBM), which induced a higher ammonia N concentration in the rumen, SRU can replace SBM in diets without affecting the growth performance of beef steers or milk production of dairy cattle (Pinos-Rodriguez et al 2010a;Pinos-Rodriguez et al 2010b).…”
mentioning
confidence: 99%
“…In this experiment, the authors observed no significant differences in DMI in treatments (P >0.05) (Table 3), though DMI was higher in the cows fed diets containing SRU. Corte et al (2018) conducted the same research in Nellore steers and observed no difference in DMI. In contrast, Galina et al (2003) conducted similar research on sixty zebu steers and reported that supplementing 1.8 g/kg DM SRU improved DMI and digestibility.…”
Section: Resultsmentioning
confidence: 94%
“…When energy is available, the final products of protein breakdown (peptide, amino acid and NH 3 -N) can be used to make the microbial protein (Bach et al, 2005). It seemed that microbial protein increase in treatment 4, is due to slow and continuous release of nitrogen from SRU (Corte et al, 2018). Therefore, the ruminal NH 3 -N concentration has an impact on MPS, and a synchrony of these processes would improve the efficiency of NPN incorporation into microbial protein and thereby improving the overall efficiency of N use.…”
Section: Microbial Protein Synthesismentioning
confidence: 99%